Qualitative Comparative Analysis : Exploring Causal Links for Scaling Up Investments in Renewable Energy - Rubinson, Claude; Jayawardena, Migara; Watkins, Ryan; Butscher, Joy; Berrah, Noureddine (World Bank, Washington, DC, 2022)
This paper uses Qualitative Comparative Analysis (QCA) to validate the theory of change developed for an evaluation of renewable energy strategies, identifying pathways for scaling up RE in a variety of different contexts. QCA was used to translate qualitative judgements into quantitative information, triangulating findings from other methods and helping to draw conclusions on how best to meet global energy goals established by the international community. The analysis also helped identify three specific pathways through which precondition barriers could be addressed to overcome challenges facing the successful achievement of the clean energy transition.